Improved skeletal muscle energy metabolism relates to the recovery of β cell function by intensive insulin therapy in drug naïve type 2 diabetes. Issue 7 (27th May 2019) - Tang, Wenjuan; Zhang, Bing; Wang, Huiting; Li, Ming; Wang, Hongdong; Liu, Fangcen; Zhu, Dalong; Bi, Yan
Abstract: Aims: Diminished energy turnover of skeletal muscle is involved in the development of type 2 diabetes. Intensive insulin therapy has been reported to maintain glycaemic control in newly diagnosed type 2 diabetes, while the underlying mechanism remains unclear. Herein, we aimed to characterize the contribution of muscular mitochondrial oxidative phosphorylation (OxPhos) activity to insulin‐induced glycaemic control. Materials and methods: There were 21 drug naïve patients with type 2 diabetes receiving continuous subcutaneous insulin infusion for 7 days. Nine nondiabetics matched for age, body mass index, and physical activity were recruited as controls. We applied 31 P magnetic resonance spectroscopy to record in vivo muscular phosphocreatine (PCr) flux in controls and diabetics before and after insulin therapy. The mitochondrial OxPhos rate was calculated as ΔPCr / Δtime during the first 50 seconds after cessation of exercise. Results: In drug naïve type 2 diabetes, muscular mitochondrial OxPhos rate was restored after insulin therapy. Notably, this alteration was positively associated with the improvements of 1, 5‐anhydroglucitol, a serum marker for glucose control over the last 1 week, as well as homeostasis model assessment of β cell function and C‐peptide/glucose ratio t 0, two indices for basal insulin secretion. Furthermore, patients with diabetes family history and more severe glucotoxicity tend to achieve greater improvement in mitochondrial function by insulin. Conclusions: This study provides evidence that intensive insulin therapy facilitates muscular energy metabolism in drug naïve type 2 diabetes. It correlates to the recovery of β cell function, contributing to insulin‐induced glucose control.